RSS - optymalny sposób zarządzania informacją - Kaczmarek-Śliwińska, Monika (RRS-Technology as Optimum Method of Information Management, 2005)
This paper introduces RSS Technology and describes its importance in management information system. RSS stands for Really Simple Syndication or Rich Site Summary and it is a web syndication format. According to BBC, this format represents a future of the web. The author demonstrates practical use of the tool and its advantages together with Polish version.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 174-182